2004
DOI: 10.1093/sleep/27.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography Performed in the Unattended Home Versus the Attended Laboratory Setting—Sleep Heart Health Study Methodology

Abstract: Using SHHS methodology, median RDI was similar in the unattended home and attended laboratory setting with differences of small magnitude in some sleep parameters. Differences in RDI between settings resulted in a rate of disease misclassification that is similar to repeated studies in the same setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 11 publications
6
117
0
Order By: Relevance
“…Elimination of the subset of subjects with a short total sleep time did not influence the principal results of the study. This procedure may be argued to have changed the validity of the sleep recordings, however, many studies have shown the similarity of in-lab PSG and home PSG [44,45]. A considerable proportion of the cases in this study were taking antihypertensive medications.…”
Section: Discussionmentioning
confidence: 82%
“…Elimination of the subset of subjects with a short total sleep time did not influence the principal results of the study. This procedure may be argued to have changed the validity of the sleep recordings, however, many studies have shown the similarity of in-lab PSG and home PSG [44,45]. A considerable proportion of the cases in this study were taking antihypertensive medications.…”
Section: Discussionmentioning
confidence: 82%
“…The current authors had a comparatively low signal failure rate, possibly due to the limited mobility of the present patient group and sensor displacement being lessened by mask and headgear use during the studies. Home polysomnography appears to have no ''first night effect'' [24], and the evidence suggests that the two scenarios can produce comparable results in respiratory and sleep data [21,25]. In the current study, the effect of study location was minimised by limiting patients to the same location for both polysomnographic studies.…”
Section: Limitations Of the Studymentioning
confidence: 76%
“…For the present analysis, AHI was obtained with the use of apneas and hypopneas associated with at least 4% oxyhemoglobin desaturation. The intraclass correlation of AHI was 0.75 between unattended home and attended laboratory settings 27 and 0.80 for night-to-night variability in the unattended home setting. 28 The interscorer reliability for scoring AHI in the SHHS was also excellent, with an intraclass correlation of 0.99.…”
Section: Polysomnographymentioning
confidence: 89%